2007
DOI: 10.2169/internalmedicine.46.6156
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Refractory Wegeners Granulomatosis Successfully Treated with Rituximab

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 20 publications
2
32
0
Order By: Relevance
“…Multiple courses of rituximab effectively induced further remissions following relapses, and re-treatment on a preemptive basis resulted in sustained remissions. These results are consistent with those of previous studies (9,(12)(13)(14)(15)(16)(17)(18)(19)(20). This is the largest series reported to date, and it pools the results from 4 UK centers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Multiple courses of rituximab effectively induced further remissions following relapses, and re-treatment on a preemptive basis resulted in sustained remissions. These results are consistent with those of previous studies (9,(12)(13)(14)(15)(16)(17)(18)(19)(20). This is the largest series reported to date, and it pools the results from 4 UK centers.…”
Section: Discussionsupporting
confidence: 92%
“…In studies of small numbers of patients, rituximab has been associated with high rates of remission, often Ͼ80%, in patients with vasculitis that had been refractory to standard therapies (9,(12)(13)(14)(15)(16)(17)(18)(19). Relapses of vasculitis following rituximab therapy have occurred, although efficacy with second and subsequent courses of rituximab has been reported (9,13,14).…”
mentioning
confidence: 99%
“…29 RTX was actually effective for one patient who suffered from intractable HP which was resistant to other conventional immunosuppressive agents, and the efficacy of RTX has also been reported in some cases of refractory HP associated with AAV. [30][31][32] Additionally, favorable outcomes were achieved with the combination of MTX and PSL in patients who indicated HP as initial and/or limited involvement without another severe visceral disorder, suggesting the concomitant use of MTX may be useful for improving HP associated with AAV unless other life-threatening organ impairment is involved. Considering not only our favorable results but also the inferiority of PSL monotherapy as previously Figure 2 Representative findings of thickened dura mater with gadolinium (Gd)-enhancement on T1-weighted image, and histopathological examination.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports suggest a beneficial effect of anti-B cell treatment in refractory orbital granulomas [18][19][20]. Taylor et al [21] recently reported beneficial effect of RTX treatment in seven patients with granulomatous orbital disease who all entered remission within 2-7 months without relapse.…”
Section: Discussionmentioning
confidence: 99%